An efficient exact hypercube model with fully dedicated servers - Beojone, Caio Vitor [UNESP]; de Souza, Regiane Máximo [UNESP]; Iannoni, Ana Paula (Institute for Operations Research and the Management Sciences (INFORMS), 2021)
The hypercube model is a useful descriptive tool to evaluate emergency services such as firefighters, police, and emergency medical services where geographically distributed vehicles and personnel serve users in emergencies. This study proposes an extension of the hypercube model to represent a dispatch policy in which advanced equipped servers serve solely life-threatening calls (called dedicated servers). The proposed approach is applied to two case studies of public medical emergency services in two different cities in Brazil and validated with discrete-event simulations. The computational experiments show the proposed model as more sensitive to respond to more life-threatening requests than other hypercube models in the literature, serving more of these requests under increased demand. In addition, to reduce the number of equilibrium equations and, consequently, the computational effort of the hypercube model, an aggregate model is shown based on the grouping of homogeneous servers located in the same station. The aggregation policy does not generate additional losses in the accuracy of the model, as shown through several experiments.
Keywords: Aggregation of states; Distinct servers; Emergency medical services; Probabilistic location model; Queueing theory